Improving Students’ Ability in Writing Procedure Text by Using Demonstration in SMKN 1 Makassar - Andi Alif Batara; Haryanto Atmowardoyo; Amirullah Abduh (Journal of Excellence in English Language Education, 2023)
The problem statement was: What is the students’ ability before and after the demonstration treatment? And does the demonstration method improve student’s ability in writing procedure text? The method that this research used was a pre-experimental design, where it uses a one-group pre-test and post-test design. The sampling method used a simple random sampling technique, where the result of the random sampling is 2 classes of any department that are available in Vocational High School 1 Makassar are being taken randomly. A class from the Accountant department and a class from Travel and Tourism Business department are taken as the result of the random sampling. The students’ ability in writing procedure text will be tested through pre-test and post-test. Student’s ability in writing Procedure Text will be analyzed and calculated based on 5 criteria/proficiencies; Content, Organization, Language Use, Mechanics, and Vocabulary. The research results that 2nd Grade students in SMKN 1 Makassar have improved their ability in writing Procedure Text. It can be seen both from pre-test results and post-test results. The pre-test overall score is 60,6, which is categorized into the “not competent” category, and the post-test overall score is 77 which is categorized as a “competent” category. It also passes the standard score to reach the “competent score”, which is 70. In other words, the improvement of the 2nd-grade of students in SMKN 1 Makassar can be seen through the post-test results.